Methods effects in factorial surveys: An analysis of respondents' comments, interviewers' assessments, and response behavior - Carsten Sauer; Katrin Auspurg; Thomas Hinz; Stefan Liebig; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper describes the implementation of a factorial survey within the SOEP-Pretest of 2008 and investigates (1) respondents' comments about the vignettes, (2) interviewers' assessments of respondents comprehension and willingness to answer, and (3) response behavior regarding response time, use of the answering scale, and consistency of evaluations by different age groups and educational background. The respondents evaluated 24 vignettes consisting of ten dimensions that described full-time employees and their gross earnings. The evaluation task was to assess whether the given earnings were just or unjust, and if they were rated as unjust, respondents had to specify the amount of injustice on an 100-point rating scale. In regard to respondents' comments, the critique mentioned most frequently by respondents referred to the content (unrealistic descriptions) and the number of the vignettes. The analysis of the interviewers' assessments of respondents' comprehension and willingness to answer revealed less comprehension and willingness to answer for older and less well educated respondents, although these differences were similar to those found for the complete questionnaire. The analysis of the response behavior revealed no di erences of response time between the groups. Analyses of response consistency show that one should consider hints for simplifying heuristics: such heuristics can lead to an artificially high response consistency. The implications of the findings are discussed.
Keywords: C81; D63; J31; 330